1987
DOI: 10.1177/030098588702400410
|View full text |Cite
|
Sign up to set email alerts
|

Spastic Syndrome in a Holstein Bull: A Histologic Study

Abstract: Abstract.A 4-year-old Canadian holstein bull developed the spastic syndrome, an episodic but progressive disorder causing pelvic limb muscular spasms. A post-mortem study, including morphometry of skeletal muscles and teased peripheral nerve fibers of the pelvic limb, revealed mild type I1 skeletal muscle fiber atrophy and minimal, focal segmental demyelination with remyelination, and axonal degeneration in peripheral nerves. Such alterations are probably incidental or age-associated. Idiopathic muscular cramp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Frauchiger and Hofmann 7 (1941) were also not able to observe histological changes in the CNS. Wells et al 13 reported (histo-)pathological lesions in a 4-year-old Canadian Holstein bull with a mild form of spastic syndrome (widespread arthroses among 16 31 Three (rather four) to seven years 1 Clinical signs Progressive hyperextension of the hindlimb(s) and contraction of the Achilles tendon caused by persistent spasms of certain muscles 16 Hyperextension of the hindlimb(s) caused by recurrent and reversible clonic and tonic muscular cramps 16 Affected areas of the body Hindlimb(s), unilateral or bilateral 16 Hindlimb(s), unilateral or bilateral; and with progression of the disease also back and neck muscles 16 Treatment Surgical treatment possible 16 52 Only symptomatic treatment possible 1 Similarities Clinical signs and affected areas of the body ► Unilateral or bilateral afection of the hindlimb(s) ► Oten an increased angle of the ankle joint ► Clinical signs appear only in rising, standing and moving animals (never in lying animals) ► No recovery of the clinical signs 16 53 other things; minimal changes in mixed and cutaneous peripheral nerves, sparse focal myelin degeneration, occasional ibres with intramyelinic bubbles in the lumbar and sacral dorsal roots; eosinophilic bodies in the nucleus gracilis). However, none of these indings were expected by the authors to account for the observed clinical signs.…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…Frauchiger and Hofmann 7 (1941) were also not able to observe histological changes in the CNS. Wells et al 13 reported (histo-)pathological lesions in a 4-year-old Canadian Holstein bull with a mild form of spastic syndrome (widespread arthroses among 16 31 Three (rather four) to seven years 1 Clinical signs Progressive hyperextension of the hindlimb(s) and contraction of the Achilles tendon caused by persistent spasms of certain muscles 16 Hyperextension of the hindlimb(s) caused by recurrent and reversible clonic and tonic muscular cramps 16 Affected areas of the body Hindlimb(s), unilateral or bilateral 16 Hindlimb(s), unilateral or bilateral; and with progression of the disease also back and neck muscles 16 Treatment Surgical treatment possible 16 52 Only symptomatic treatment possible 1 Similarities Clinical signs and affected areas of the body ► Unilateral or bilateral afection of the hindlimb(s) ► Oten an increased angle of the ankle joint ► Clinical signs appear only in rising, standing and moving animals (never in lying animals) ► No recovery of the clinical signs 16 53 other things; minimal changes in mixed and cutaneous peripheral nerves, sparse focal myelin degeneration, occasional ibres with intramyelinic bubbles in the lumbar and sacral dorsal roots; eosinophilic bodies in the nucleus gracilis). However, none of these indings were expected by the authors to account for the observed clinical signs.…”
Section: Aetiopathogenesismentioning
confidence: 99%
“…To our knowledge, this is the first investigation coupling the morphology and the function of Rexed's lamina IX in the lumbosacral region of the spinal cord of cattle. Results of this research could be useful for studying other bovine neuronal diseases involving the lumbosacral region of the spinal cord and its afferent pathways, such as spastic syndrome (standing disease) of adult cattle 20 or bovine spinal muscular atrophy. [21][22][23][24] We also investigated, by use of immunohistochemical procedures, substance P (SP), calcitonin generelated peptide (CGRP), galanin (GAL), and neuronal nuclear protein (NeuN) immunoreactivity of neurons.…”
mentioning
confidence: 99%
“…Regarding LOC100848076, no animal models or human disease has been reported so far. In one BSS case report, demyelination was detected, which was later interpreted as a link to multiple sclerosis (Wells et al, 1987;Goeckmann et al, 2018). However, similar lesions were later identified also in Charolais cattle with progressive ataxia and American Brown Swiss with spinal demyelination (Thomsen et al, 2010;Duchesne et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…So far, no functional pathway or genetic background was identified to enlighten its pathogenesis. Solely one pathological examination of a BSS-affected bull reports focal demyelination (Wells et al, 1987). In fact, for BSP, a decreased concentration of homovanillic acid in the cerebrospinal fluid was measured (De Ley and De Moor, 1975).…”
Section: Introductionmentioning
confidence: 99%